The diversity of plankton as bioindicators in Kakap River Estuary, West Kalimantan - Widadi Padmarsari Soetignya; Patrisia Marniati; Mardan Adijaya; Yunita Magrima Anzani (Depik, 2021)
Kakap River Estuary plays an essential role in the life organisms, but it is vulnerable to environmental changes and pollution caused by human activities. This study aims to assess the presence of plankton species, their abundance and diversity as aquatic ecological bio-indicators in Kakap River Estuary. Plankton and water samples were taken for three months, with a frequency of one sample per month, viz. in March, April and June 2020 from four sampling stations in Kakap River Estuary, West Kalimantan. A total of 34 species of plankton were observed from all sampling sites, and identified to belong to 18 classes. Chlorophyceae had the highest relative abundance among the phytoplanktons (40.10%), followed by Bacillariophyceae (21.86%) and Cyanophyceae (19.28%). Oscillatoria sp. and Hydrodictyon sp. were the most dominant phytoplankton species. There were 8 classes of zooplankton identified from all sampling stations throughout the research period. Hexanauplia had the highest relative abundance among the zooplanktons (36.56%) followed by Euglenophyceae (24.37%). The plankton diversity index (H ) values ranged between 2.33 -3.11. The plankton evenness index value ranged from 0.79 to 0.89 which indicates high plankton evenness at all samping stations, and this is supported by a low dominance index value at all stations ranging from 0.06-0.16. Station 1 had high Shannon-Wienner diversity index score, while for station 2, 3, 4, their scores were in the moderate level. Overall. the diversity index of the plankton from all sampling sites indicated that the quality of the water had no pollution to light pollution level.Keywords:PhytoplanktonZooplanktonWater quality